TINJAUAN LITERATUR KRITIS ATAS KONSEP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fadillah, Muhammad Ifan (Jurnal Manajemen & Bisnis Jayakarta, 2024)
This article will try to explore further the concept of organizational citizenship behavior (OCB). The concept of organizational citizenship behavior is commonly used by academics and researchers to support the concept of OCB in terms of improving the performance of human resources in an organization or company. This article will present a different perspective. Instead of using the OCB concept to enhance human resource performance, this article will demonstrate that the OCB concept is actually a form of exploitation by capital owners towards workers, which possesses a unique humanitarian approach. The method used in this research is a literature review with Marxist analysis which sees the problematic field as an economic basis, namely class